UK Ocean Acidification programme surface carbonate chemistry measurements from D366 cruise around the British Isles. - Ribas Ribas, Mariana; Rerolle, Victoire; Kitidis, Vassilis; Bakker, Dorothee C E; Lee, Gareth A; Brown, Ian; Hardman-Mountford, Nick; Stinchcombe, Mark; Palmer, Matthew (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
This dataset is a synthesis of the carbonate chemistry measurements made on surface samples collected on RRS Discovery cruise D366. The cruise was the first of three cruises undertaken by the Sea Surface consortium of the UK Ocean Acidification (UKOA) programme. The cruise took place in the northwestern European shelf seas around the British Isles during June and July 2011. Participants from UoS, NOCS, UEA and PML between them measured five independent carbonate chemistry variables (pCO2 *2, TA, DIC, pH) and inorganic nutrients from surface waters during the cruise. Samples were collected from the ship's non-toxic supply with a nominal intake depth of 5m. During the cruise the analyses for each measurement followed the standard protocols detailed below. After the cruise the data were aggregated for a complete quality control and intercomparison exercise. Calibrated salinity and temperature from the ship’s underway system as processed by NOCL are included as ancillary data. These measurements form a subset of the observational measurements undertaken on the cruise, with the full cruise dataset inventory available from the BODC website BODC website. The collection of these data and the subsequent synthesis and intercomparison were funded as part of the UKOA programme by NERC, DEFRA and DECC.